Cystic fibrosis in Turkey: First data from the national registry. Issue 2 (11th November 2019) - Dogru, Deniz; Çakır, Erkan; Şişmanlar, Tuğba; Çobanoğlu, Nazan; Pekcan, Sevgi; Cinel, Güzin; Yalçın, Ebru; Kiper, Nural; Şen, Velat; S. Şen, Hadice; Ercan, Ömür; Keskin, Özlem; et al.
Abstract: Background: Cystic fibrosis (CF) care has been implemented in Turkey for a long time; however, there had been no patient registry. For this purpose, the Turkish National CF Registry was established. We present the first results of registry using data collected in 2017. Methods: The data were collected using a data‐entry software system, which was accessed from the internet. Demographic and annually recorded data consisted of 15 and 79 variables, respectively. Results: There were 1170 patients registered from 23 centers; the estimated coverage rate was 30%. The median age at diagnosis was 1.7 years (median current age: 7.3 years); 51 (4.6%) patients were aged over 18 years. Among 293 patients who were under 3 years of age, 240 patients (81.9%) were diagnosed through newborn screening. Meconium ileus was detected in 65 (5.5%) patients. Genotyping was performed in 978 (87.4%) patients and 246 (25.2%) patients' mutations were unidentified. The most common mutation was deltaF508 with an allelic frequency of 28%, followed by N1303K (4.9%). The median FEV1% predicted was 86. Chronic colonization with Pseudomonas aeruginosa was seen in 245 patients. The most common complication was pseudo‐Bartter syndrome in 120 patients. The median age of death was 13.5 years in a total of 15 patients. Conclusions: Low coverage rate, lack of genotyping, unidentified mutations, and missing data of lung functions are some of our greatest challenges. Including data of all centers and reducing missing data will provide more accurate data and help to improve the CF care in Turkey in the future.